2019
DOI: 10.1515/biol-2019-0039
|View full text |Cite
|
Sign up to set email alerts
|

Effects of LED light on Acacia melanoxylon bud proliferation in vitro and root growth ex vitro

Abstract: This study examines the effects of light emitting diodes (LEDs) on tissue culture proliferation of Acacia melanoxylon plantlets among five different clones (FM1, FM2, FM4, FM5, and FM10). Shoot bud apex cuttings were transplanted onto Murashige and Skoog basal medium containing 0.1 mg L-1 6-benzyladenine and 0.5 mg L-1 naphthalene acetic acid and cultured in vitro for 40 days. Root growth was studied under different light intensities and photoperiods ex vitro. The bud proliferation coefficient was greatest und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…In the present study, we found that plantlets during photoperiod 16 h showed higher height, dry weight, rooting rate, average root number, root length, root surface area, and volume at most light qualities compared to photoperiods 8, 24 h. And the best plantlets were harvested with more roots and leaves. Similar results were reported by Li et al [24], the plantlet growth and root growth of Acacia melanoxylon found to be the highest among in vitro culture under photoperiod 16 h. Plants mainly perceive light signals through photoreceptors such as red/far red light receptors, blue/near ultraviolet photoreceptors, and ultraviolet photoreceptors, to regulate plant growth and physiological metabolism [19,25]. Our results showed that plant height, rooting rate, root length, root surface area and root volume of R/B/P/G were higher than R/B, R/B/P and W under photoperiods 8 and 16 h, while they were lower in the R/B, R/B/P than W, suggesting that the red-blue-purple-green composite light could increase growth of C. lanceolata in vitro culture plantlets.…”
Section: Growthsupporting
confidence: 92%
“…In the present study, we found that plantlets during photoperiod 16 h showed higher height, dry weight, rooting rate, average root number, root length, root surface area, and volume at most light qualities compared to photoperiods 8, 24 h. And the best plantlets were harvested with more roots and leaves. Similar results were reported by Li et al [24], the plantlet growth and root growth of Acacia melanoxylon found to be the highest among in vitro culture under photoperiod 16 h. Plants mainly perceive light signals through photoreceptors such as red/far red light receptors, blue/near ultraviolet photoreceptors, and ultraviolet photoreceptors, to regulate plant growth and physiological metabolism [19,25]. Our results showed that plant height, rooting rate, root length, root surface area and root volume of R/B/P/G were higher than R/B, R/B/P and W under photoperiods 8 and 16 h, while they were lower in the R/B, R/B/P than W, suggesting that the red-blue-purple-green composite light could increase growth of C. lanceolata in vitro culture plantlets.…”
Section: Growthsupporting
confidence: 92%
“…Under equal DLI, higher root activity was observed in those cucumber seedlings exposed to supplementary light with a longer photoperiod at 10 h d -1 and 12 h d -1 (Figure 3D). Li et al [58] demonstrated that the average root number of Acacia melanoxylon increased significantly with a prolonged photoperiod, but this trend was not observed in the average root length. A large root absorption area with higher root activity promoted plant growth, which was consistent with other reports [59].…”
Section: Influences Of Supplementary Light Duration and Light Intensity On Plant Morphology And Growth Of Cucumber Seedlingsmentioning
confidence: 99%
“…Monochromatic blue LEDs were more effective on the biomass compared with the red, B3R7 LEDs, and control light treatments. Most studies have demonstrated that BR-combined LED lights contribute to an enhanced overall plant biomass compared with other light treatments [ 14 , 18 , 19 , 32 , 33 ]; however, it was not applicable for H. corymbosa in vitro. There was no fresh and dry weight difference measured between all combinations of the BR combination LEDs and the control light ( Figure 1 C,D).…”
Section: Resultsmentioning
confidence: 99%